Antidiarrhoeal effects of Mikania glomerata Spreng. (Asteraceae) leaf extract in mice - Salgado, Hérida Regina Nunes [UNESP]; Roncari, Ana Flávia F. [UNESP]; Moreira, Raquel R.D. [UNESP] (Sociedade Brasileira de Farmacognosia, 2005)
Mikania glomerata Spreng. (Asteracae) is a plant widely used to treat gastrointestinal disorders in Brazilian traditional medicine. In the present work, an aqueous extract of the leaves of Mikania glomerata has shown a decrease in the propulsive movements of the intestinal contents in mice. Oral administration produced an inhibition of gastrointestinal transit as effective as that produced by loperamide. These findings suggested that the aqueous extract of the leaves of Mikania glomerata might elicit an antidiarrhoeal effect by inhibiting intestinal motility.
Keywords: Mikania glomerata; Asteraceae; guaco; intestinal motility